The Application of Anatomy Combined With Ultrasound Knife in Transaxillary Endoscopic Biplane Breast Augmentation - Xiong, Jiachao; Hou, Qiang; Hu, Zheyuan; Gao, Yakun; Lu, Lu; Sun, Meiqing; Hu, Hao; Qian, Yuxin; Wang, Hui; Jiang, Hua (Frontiers in Surgery, 2022)
Objective We aim to clarify the vascular and nerve anatomy of the breast and combine it with an ultrasound knife to use in transaxillary endoscopic biplane breast augmentation. Methods This study is a retrospective review of patients undergoing transaxillary endoscopic biplane breast augmentation between October and October 2021. Related variables were collected using a standardized data collection template. The detailed process of the transaxillary endoscopic biplane breast augmentation under anatomy instruction is carefully described in this study, and the postoperative effect was closely observed. Results Sixty-three female patients underwent transaxillary endoscopic biplane breast augmentation. The average implants volume counted 242.46 ± 31.34 cc, and the average operation time was 155.92 ± 22.34 min. Patients were followed up for a mean of 13.67 months (range, 3–27 months), and most of the patients achieved good postoperative results and no severe complications and were satisfied with both appearance and function. Conclusions The application of anatomy combined with an ultrasound knife in transaxillary endoscopic biplane breast augmentation is a promising way to achieve good breast shapes with high patient satisfaction and is worthy of clinical promotion and application.